STRATEGIES FOR INCREASING THE EFFICIENCY OF THE DENTAL PRACTICE ACTIVITY - PART II - Lupu Iulian Costin; Mihăilă Constantin Bogdan; Ovidiu Stamatin; Roxana Ionela Vasluianu; Doriana Agop-Forna; Tibeică Silviu Cătălin; Consuela Norina Forna (Romanian Society of Oral Rehabilitation, 2023)
Dentists are constantly looking for strategies to make their work more efficient. These strategies are related to different aspects regarding the organizational activity of the dental practice, with the aim of achieving an improvement in the dental services offered. In the first part of the article, we presented some of the strategies that can be used, such as the creation and implementation of a standardized protocol for the entire team that, in addition to operating times, also provides for the necessary tool kits and cutters, all in an ergonomic environment and with an efficient organization of the workspace. The method of working at "4 hands" will increase the fluidity and focus during the procedures, which leads to a shorter working time with the aim of a predictable treatment and a dental service of an improved quality. These strategies can only be implemented by a responsible team based on quality professional communication. The application of these strategies can significantly streamline the activity of the dental office, bringing financial and human benefits and an increase in the quality of the medical act in a less stressful environment without an increase in fees.